Beyond the Spectrum: Rethinking Autism - Thomas, Heather; Boellstorff, Tom (Disability Studies Quarterly, 2017)
The "spectrum" has become the dominant metaphor for conceptualizing autism, with fundamental consequences for notions of disability, diversity, and normality. In this article, we draw on ethnographic research with autistic communities to explore how the notion of the autism spectrum has become a focus of explicit identification, reflection, and contestation. To further this inquiry, we place these debates into conversation with earlier debates regarding another spectrum—the Kinsey Scale, a "spectrum" for conceptualizing sexual orientation that first appeared in 1948 but has been critiqued since the 1970s. How might responses to the Kinsey Scale (like the Klein Grid) contribute to rethinking the autism spectrum? This is a question about the cultural and political implications of metaphors and conceptual models. It is of broad importance because the spectrum metaphor is being extended to a range of conditions beyond autism itself. Our goal is thus to build on insights from sexuality studies as well as the insights of autistic persons, advocates, and researchers who wish to forestall the naturalization of "the spectrum." In doing so, we seek to contribute to a discussion of what alternative frameworks might bring to questions of social justice, ability, and human flourishing.